Governança e cooperação no desenvolvimento de arranjos produtivos locais : estudo de casos múltiplos de APL em Sergipe - Aragão, Aline Menezes de (2011)
Local clusters have been presented as a strategy for micro, small and medium enterprises to increase their survival chances and overcoming the barriers to growth. This study aimed to examine how governance and cooperation among institutional and economic agents can influence the development of local clusters in the state of Sergipe. Methodological procedures were used for the case study and it was adopted a perspective cross-sectional analysis. The analysis level was the cluster and the analysis unit were the institutional and economic agents. Thirty-two semi-structured interviews were conducted with clusters agents in Sergipe. Based on the cases analysis it was observed that the clusters analyzed wee predominantly composed by micro and small enterprises with low technology that operate in local and regional markets. The largest clusters in relation to production units and formal jobs generation were Itabaianinha Red Ceramics and Tobias Barreto Clothing. The nature of coordination and networking among firms tends to be low with tough competition and reduced confidence. It was verified that the private governance of Red Ceramics of Low São Francisco and Itabaianinha Clothing clusters have been the most active, which has enabled more diverse cooperation actions between economic and institutional actors.